Quantitative synthesis of protein–DNA conjugates with 1 : 1 stoichiometry. Issue 54 (19th June 2018) - Yan, Xiaowen; Zhang, Hongquan; Wang, Zhixin; Peng, Hanyong; Tao, Jeffrey; Li, Xing-Fang; Chris Le, X.
Abstract : We describe here a binding-facilitated reaction strategy, enabling quantitative conjugation of DNA to native proteins with a desirable 1 : 1 stoichiometry. Abstract : We describe here a binding-facilitated reaction strategy, enabling quantitative conjugation of DNA to native proteins with a desirable 1 : 1 stoichiometry. The technique takes advantage of the iterative affinity interaction and covalent binding processes to achieve complete conjugation. The complete conjugation obviates the need for separation of the protein–DNA conjugates as required by other DNA–protein conjugation methods.